Pemberdayaan Guru Al-Qur’an Hadis dalam Percepatan Menghafal Surat-Surat Pendek Siswa Madrasah Tsanawiyah Negeri 4 Merangin - Akhyaruddin, Akhyaruddin (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2023)
This research was conducted at MTs Negeri 4 Merangin, this research was motivated by the problem of empowering Al-Qur'an Hadith teachers towards the acceleration of memorizing short letters of Madrasah Tsanawiyah 4 Merangin students who were less than optimal. The research approach is a qualitative approach with the research subject of Al-Qur'an Hadith teachers and students. The research location is Madrasah Tsanawiyah Negeri 4 Merangin. Collecting data using observation techniques, interviews, and documentation. Data analysis techniques are data reduction, data presentation, and data verification. Based on the results of field research, several research conclusions were obtained as follows: The process of empowering teachers in the field of Al-Qur'an Hadith studies has been carried out, but in practice they still face many problems including the lack of textbooks, lack of student appreciation of memorization, and lack of time in providing teaching material.